Fine needle biopsy of pediatric‐type follicular lymphoma—Cytology, flow cytometry and FISH pattern: A case report. Issue 12 (18th August 2021) - Barroca, Helena; Marques, Cristina; Soares, Maria José; Carvalhais, Inês
Abstract: Pediatric‐type follicular lymphomas are rare lymphomas, affecting mostly children and young adults. These are characterized by an excellent prognosis, despite their conservative therapeutic approach. Recognized as an entity in the most recent 2016 WHO classification of tumors of hematopoietic and lymphoid tissues, its diagnosis is based on the recognition of an exclusively nodular architecture, thus conditioning the possibility of a cytological diagnosis. It is thus not odd, the scant literature found on the cytological approach to these lesions. Herein we describe a case of a pediatric‐type follicular lymphoma, first approached through fine needle biopsy. The case is thoroughly discussed from a cytologic, immunophenotypic, and molecular point of view. Differential diagnoses are discussed. The final diagnosis was performed on histology.